2001
DOI: 10.1016/s0168-6496(01)00177-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a rhizosphere microbial community exposed to natural and manipulated environmental variability

Abstract: Phospholipid fatty acid (PLFA) and artificial neural network analyses were used to examine the composition of the Spartina alterniflora rhizosphere microbial community after exposure to manipulations in the field designed to alter the availability of host plant-derived and abiotic nutrient resources. We also tracked the experiments over a sufficient duration to observe significant natural variability in edaphic variables. We determined the PLFA composition of axenic S. alterniflora roots in order to distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…It, however, should be noted that the effect of PLFAs derived from living rice roots could not be completely excluded. Although PLFA composition of rice roots was unavailable, the measurement of sea grass roots showed that plant roots contained mainly PLFAs 16:0, 18:2ω6c, 18:3ω3 and 18:1ω9 (over 90% of total PLFAs in the case of Spartina alterniflora ) [33]. Assuming rice roots contained similar PLFA composition, total and 13 C PLFAs, especially those of 16:0 and 18:1ω9 might be overestimated due to possible incomplete separation of living roots from soil.…”
Section: Resultsmentioning
confidence: 99%
“…It, however, should be noted that the effect of PLFAs derived from living rice roots could not be completely excluded. Although PLFA composition of rice roots was unavailable, the measurement of sea grass roots showed that plant roots contained mainly PLFAs 16:0, 18:2ω6c, 18:3ω3 and 18:1ω9 (over 90% of total PLFAs in the case of Spartina alterniflora ) [33]. Assuming rice roots contained similar PLFA composition, total and 13 C PLFAs, especially those of 16:0 and 18:1ω9 might be overestimated due to possible incomplete separation of living roots from soil.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing discharges of agricultural fertilizers into coastal ecosystems have been shown to cause a progressive transition of creek-edge and bay-edge marshes into mudflats and wider creeks worldwide (MacGarvin, 2001 ; Tiner et al, 2006 ; Deegan et al, 2012 ). Thus, to prevent such ecological distress, it is crucial to examine the capacity of salt marshes to cycle N and to deal with exogenous N influxes (e.g., Lovell et al, 2001 ; Bowen et al, 2011 ; Peng et al, 2013 ). In spite of the urgency, the current knowledge of how microbial N cycling populations are ecologically assembled in salt marshes is still rudimentary.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, whereas the ammonia-oxidizing bacteria (AOB) were found to respond to N fertilization, ammonia-oxidizing archaea (AOA) remained unaffected (Peng et al, 2013 ). Moreover, no significant effect was found on the nitrogen-fixing and denitrifying bacterial communities when exposed to added N (Piceno and Lovell, 2000 ; Lovell et al, 2001 ; Bowen et al, 2011 ). Of particular importance, and lacking in these studies, is a thorough understanding of the distribution and drivers of N cycling communities in a naturally developing salt marsh ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The diazotroph assemblages associated with salt marsh plant rhizospheres are somewhat stable. Only minor changes in the assemblages were observed when long and short-term fertilization and above ground biomass removal experiments were performed [ 29 , 30 , 31 , 79 ]. The drastic difference in the diazotroph assemblages in 2005 and 2006 as observed in DGGE band determination and deemed significant by PCA cluster analysis, indicate that the moderate drought event that occurred in 2004 directly affected these assemblages.…”
Section: Discussionmentioning
confidence: 99%